Isolasi Gen Penyandi Peroksidase melalui Penapisan terhadap Pustaka Genom Kedelai Kultivar Slamet - Suharsono, Suharsono; Rachman, Faisal; Astuti, Utut Widy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Screening to genomic library of soybean cultivar Slamet in ë phage to isolate the gene encoding for peroxidase(per) was performed by two steps. cDNA of per gene from Arabidopsis thaliana labeled by alkalin phosphatasewas used as probe. The first screening was done by using 105 recombinant pfu (plaque forming unit). The secondscreening was carried out on 100 recombinant pfu isolated from the first screening. The result of second screeningshowed that all screened clones were supposed containing per gene. The ë phage resulted from second screeningwas infected into E. coli BM 25.8. Due to the Cre recombinase in E. coli BM 25.8, two lox P sites flanking the insertDNA of soybean created recombination. The recombination in loxP sites resulted the excision and formedrecombinant plasmid containing per gene of soybean. To multiply, the recombinant plasmid was introduced into E.coli DH5á. Analysis southern hibridization of recombinant plasmid cut by Bam HI showed that Bam HI 3.7 kbfragmen of S52121R clone, 5,3 kb of S2412R clone, 2,4 and 5,3 kb fragments of S2532R clone were supposed tocontain per genes.